WAYS TO ACTIVATE THE TEACHING OF ARABIC LINGUISTICS AND ITS EFFECTS IN NON-ARABIC SPEAKERS IN MALAYSIAN UNIVERSITIES: AN ANALYTICAL DESCRIPTIVE STUDY - Asma Abdul Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The outcome of education (students) in various countries of the Islamic world and the Arab find that a large proportion of them are not at the desired level in terms of possessing the skills and abilities of language and linguistic sciences in various branches, despite the efforts made by teachers, supervisors and state institutions, but did not achieve the desired results, To heal the rift, there must be a cure for the different teaching methods and factors affecting ways of activating the methods of education. The aim of the research is to address the quality of teaching provided to students, And make the teaching effective to make the change required. The student is not in the process of learning the student is a recipient of information only, but a participant and seek information in various ways possible. The preparation of language curriculum is a pattern of teaching depends on self-activity and positive participation of the learner through which may Research, using a set of activities and scientific processes such as observation and clarification of hypotheses, measurement and reading data and conclusion, which help in obtaining the information required by himself and under the guidance of the guide and guidance, and we seek to find ways to activate the teaching of Arabic linguistics Different teaching style and its effects in non - Arabic speakers